Organoleptic and Durability of Frozen Whole Broiler Chicken Thawed with Chitosan Edible Coating for Different Shelf Life - Yusni Khairani Tampubolon; Saragih, Winda Fransisca (Jurnal Peternakan Integratif, 2025)
The increase in broiler production led to an oversupply of chicken in the market while the increase in chicken consumption was not proportional to the increase in production.  Therefore frozen storage is one of the alternatives to overcome this excess chicken production. This study aimed to determine the effect of chitosan edible coating concentration and storage time on the shelf life and organoleptic properties of frozen broiler chicken carcasses during the thawing process. This study used a Factorial Completely Randomized Design (RALF) consisting of two factors, namely Factor 1: differences in shelf life (1, 2, and 3 months) and factor 2: concentration of edible chitosan coating (0, 1%, 1.5%) with five replications. The parameters observed were shelf life and organoleptic properties (aroma, texture, color, and total acceptance). Data were analyzed using Two-way Analysis of Variance and further testing of the Duncan Multiple Range Test (DMRT). The results showed that chitosan concentration had a significant effect (P <0.05) on shelf life and organoleptic quality, whereas shelf life did not have a significant effect. The use of 1% chitosan gave the best results in organoleptic quality and 1.5% in slowing down broiler carcass decay. In conclusion, edible chitosan coatings can be effectively applied during thawing to extend the shelf life and maintain the quality of frozen broiler chicken meat